The Effect of Fly Ash Mixture on Concrete Compressive Strength - Sofia, Dewi Ayu; Kamal, Noval (Politeknik Sukabumi, 2023)
Fly ash is a waste from the steam power plant industry that can be used as added material in making concrete. This is because the chemical compounds in fly ash are almost the same as cement. The purpose of this study was to determine the compressive strength of concrete with partial replacement of cement with fly ash. The composition of partial replacement of cement with fly ash is 0%, 20%, 25%, 30%, and 35%. The planned concrete quality is Â 30 MPa and tested at the age of 7 days and 28 days. The test results show the average compressive strength of the concrete for all variations of both 7-day and 28-day replacement is less than 30 MPa. The greater composition of fly ash used, the smaller the compressive strength value of the concrete. This is caused by the slow hydration process because fly ash is pozzolans which delay the hydration process. In addition, the reduction of cement content will also result in a decrease in compressive strength, this is because the bonding capacity of the aggregate decreases. However, when viewed based on the density of the concrete, the fine fly ash grains can make the concrete denser.